Study of coupling between shaft bending and disc zero nodal diameter modes in a flexible shaft-disc assembly. (4th August 2020) - Tuzzi, G.; Schwingshackl, C.W.; Green, J.S.
Abstract: In a shaft-disk flexible assembly supported by linear bearings, the disk 1ND modes couple with the shaft lateral modes, whilst the 0ND "umbrella" modes couple with the shaft axial modes. The objective of this work is to investigate and quantify the coupling between disk 0ND modes and shaft lateral modes and its correlation with some innovative, oriented bearing supports, which couple shaft axial and lateral displacements. This phenomenon is investigated via two different models. In the first one, the shaft in isolation is considered and modelled with 1D beam elements. It is found that, if the supporting structure of the shaft is asymmetric, some lateral modes couple with the axial mode, giving rise to the so called "mixed modes". In the second part of this work, a full 3D model of the assembly is implemented and a parametric study is carried out, varying the parameters of the supporting structure (stiffness and orientation) and of the disk (position along the shaft). A physical explanation of this coupling is provided, taking into account the reaction forces/moments at the interface between shaft and disk and the dynamic response of the separate components. The limitations of the current approach to modes coupling are also highlighted throughout this work.